Aspects of tenders for construction contracts - Crail, Hugh Francis (Department of Civil Engineering, 2016)
Before considering in detail that portion of the cost of a Civil Engineering project associated with the employment of a contractor, one should take an overall look at the total cost of an average project. This would usually include the following items a) cost of the land on which the project was to be built; b) legal expense incurred in drawing up conditions of contract, etc.; c) financial expense including interest on bank loans or the cost of issuing bonds; d) cost of construction itself; e) cost of employing consulting eng1neers to design and supervise the project; f) loss of interest that could be earned by capital tied up during the construction period; g) contingencies. It is clear that while construction costs do not constitute the complete cost of a project, they nevertheless form a very large part. Hence, once the consultants have been appointed, they theoretically expend a great deal of time and energy in choosing an optimal design in close co-operation with the promoter.